Analisis Penerapan Joint Cost dalam Pengendalian Biaya Produksi pada UD. Batik Tulis Sido Makmur Sendangagung Paciran Lamongan - Agus Wahid Suyoto (Ali Institute of Research and Publication, 2026)
This study aims to analyze the application of the Joint Cost method in controlling production costs at UD. Batik Tulis Sido Makmur, Sendangagung, Paciran, Lamongan. The research employed a descriptive quantitative approach using secondary data, including production volume reports, raw material costs, direct labor costs, manufacturing overhead costs, and product selling prices for the 2024 period. Data were analyzed using the Joint Cost method with the Relative Sales Value Method to allocate joint costs to each product. The allocated costs were then compared with the company's standard costs to evaluate the effectiveness of production cost control. The results indicate that the application of the Joint Cost method generated lower production costs than the company's standard costs, resulting in favorable cost variances for sarong, jarik, gendong, bed sheet, and tablecloth products. The findings imply that the implementation of the Joint Cost method can assist companies in determining the production cost of each product more accurately and improving the effectiveness of production cost control. Keywords: Joint Cost, Production Cost Control, Joint Costs, Batik Industry, Cost Efficiency